Superman's not coming : our national water crisis and what we the people can do about it - Brockovich, Erin; Boothby, Suzanne (New York : Random House Audio, 2020)
"Water. The single most necessary element to sustain life. Brockovich warns that America's water crisis isn't looming on the horizon--it's already here. Superman Isn't Coming makes clear that the most precious resource on planet Earth is alarmingly polluted by toxins, hazardous waste, lead, fracking chemicals, and more. In the 20 years since her eponymous film, Brockovich has kept up the fight for clean water one town at a time. She receives thousands of letters each month from people across the country writing to her with water concerns regarding chemicals,who don't know who else to turn to. Brockovich has become a modern-day superhero responding to pleas for help throughout our country, from citizens whose letters and pleas have been ignored by their local representatives, the EPA, the Department of Natural Resources, the CDC, their local water authority with troubling situations that go unheeded and conditions not magically righting themselves. Brockovich can't fight all the fights and save our water on her own. The simple truth is that Superman isn't coming to save us. Her book is an urgent call for all of us. And in it, Brockovich makes clear why we are in the trouble we're in, and how we each can take small and large actions and change troubling conditions. She writes about the effects of climate change that have caused droughts in some areas and flooding in others, and shows how this is affecting us economically as well as destroying lives and property. She lays out the facts, and gives us the tools to take steps--large and small--to make changes in our own counties, cities and towns, and help to preserve our selves, our water, our planet"--
Introduction -- The scary truth. How did we get here? -- It began in Hinkley... and it's everywhere now -- Connecting the dots & building a map -- Floating in a sea of chemicals -- The top toxins -- The hopeful future. The communities rising -- Saying no to "unintended consequences" -- Local politics run amok -- Heroes fighting pollution at military bases -- Taking back the EPA & Florida's shorelines -- The final call. Day zero -- Time to act!
Includes index.
Keywords: Water -- Pollution -- United States; Water-supply -- United States